2006
DOI: 10.1159/000091301
|View full text |Cite
|
Sign up to set email alerts
|

Serum IGF-I and IGFBP-3 Levels of Turkish Children during Childhood and Adolescence: Establishment of Reference Ranges with Emphasis on Puberty

Abstract: Aims/Methods: We established age- and sex-related reference ranges for serum insulin-like growth factor-I (IGF-I) and insulin-like growth factor binding protein-3 (IGFBP-3) levels in 807 healthy Turkish children (428 boys, 379 girls), and constructed a model for calculation of standard deviation scores of IGF-I and IGFBP-3 according to age, sex and pubertal stage. Results: Serum IGF-I and IGFBP-3 concentrations tended to be higher in girls compared to boys of the same ages, but the differences were statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 73 publications
7
40
2
Order By: Relevance
“…Physiological differences between the sexes regarding IGF-I metabolism exist. We found higher IGF-I concentrations in girls, which is consistent with results from other studies (Kaplowitz et al, 1982;Juul et al, 1997;Garnett et al, 1999;Kawai et al, 1999;Hoppe et al, 2004b, c;Bereket et al, 2006). The metabolism of IGF-I also seems to differ between boys and girls as it was found that 9-year-old boys excreted more urine (u) IGF-I per unit u growth hormone (GH) than the girls of the same age (Fall et al, 2000).…”
Section: 00supporting
confidence: 91%
“…Physiological differences between the sexes regarding IGF-I metabolism exist. We found higher IGF-I concentrations in girls, which is consistent with results from other studies (Kaplowitz et al, 1982;Juul et al, 1997;Garnett et al, 1999;Kawai et al, 1999;Hoppe et al, 2004b, c;Bereket et al, 2006). The metabolism of IGF-I also seems to differ between boys and girls as it was found that 9-year-old boys excreted more urine (u) IGF-I per unit u growth hormone (GH) than the girls of the same age (Fall et al, 2000).…”
Section: 00supporting
confidence: 91%
“…We explored the differences between our model and reference curves for IGF-1 as a function of age and puberty stage generated from published data, by plotting the sex-specific median curves of 6 databases (7,8,10,11,14,15,19 ) together with our data.…”
Section: Discussionmentioning
confidence: 99%
“…Known determinants of these biological parameters include age, sex, and puberty, together with genetic and ethnic factors (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). There is some concern that auxological parameters may modify serum concentrations.…”
mentioning
confidence: 99%
“…For each gender, height, weight, BMI, MPH, IGF-1 and IGFBP-3 were transformed to SDSs by using Turkish reference data according to age in 1 year interval (Neyzi et al, 1973; Growth, IGF-I, IGFBP-3 levels and economic status S Turan et al Bereket et al, 2006;Bundak et al, 2006). The effect of economic status (ES) on height SDS, weight SDS, BMI SDS, MPH SDS, IGF-1 SDS and IGFBP-3 SDS was analyzed by oneway ANOVA.…”
Section: Statisticsmentioning
confidence: 99%